Capillary wicking in a fibrous reinforcement – Orthotropic issues to determine the capillary pressure components. (October 2015) - Pucci, Monica Francesca; Liotier, Pierre-Jacques; Drapier, Sylvain
Abstract: Capillary pressure effect is one of the most critical issues to understand void formation mechanisms in LCM processes. However characterisation of capillary pressure exhibits complex phenomena controlling directional flow at several scales of observation. In the present study a new definition of capillary pressure P cap and an experimental technique to determine it are described. Wicking tests at the scale of the fabric have been carried out with a tensiometric technique. A good agreement with the Washburn equation has been shown and an equivalence with Darcy law has been proposed. This technique was extended to the measurement of capillary pressure in the three principal directions on a classical quasi-UD carbon fabric. This first approach performed with test liquids (water), will be conducted on other reinforcements and fluids to be more relevant with the final application: LCM processes.